Leakage Detection System in Water Pipeline Distribution Simulator Using Point Pressure Analysis Method - Alfin Sahrin; Wildan Rafsanjani; Chalidia Hamdani (G-Tech: Jurnal Teknologi Terapan, 2026)
Water leakage in pipeline networks leads to significant non-revenue water losses, often exceeding 30% in various regions. This study aims to develop an innovative leakage detection system using the Point Pressure Analysis (PPA) method integrated with Internet of Things (IoT) technology. The objective is to accurately detect the location and estimate the volume of leakage in real time. A prototype pipeline system was constructed using PVC pipes, equipped with three pressure sensors and two flow rate sensors. Data were collected using a NodeMCU ESP8266 and transmitted to the Blynk (mobile) and LabVIEW (PC) platforms. Leak simulations were performed were conducted by varying valve openings at 10°, 30°, 60°, and 90°, resulting in pressure drops from 55 kPa (no leak) to 48 kPa, 40 kPa, 34 kPa, and 29 kPa respectively. The system successfully detected leakage locations with 98.3% accuracy and estimated leakage volume with an average error of 3.2%, demonstrating its effectiveness and reliability for water monitoring applications.